Moral Values Pertained in The Movie Entitled "The Pursuit Of Happyness” Directed by Gabriele Muccino - Tahrun Tahrun; Mulyadi Mulyadi; Arya Fitri (Journal of English Education and Teaching, 2023)
This research aimed to found the Moral values, Intrinsic elements, in the movie and also theoretical implication for English Language Teaching. Every movie has intrinsic elements and moral value to be discovered to its viewers. In movie "The Pursuit of Happyness” Directed by Gabriele Muccino. intrinsic elements were discovered through the elements in the movie and moral values through the characters in the movie. The objectives of the research were to investigate the moral values and intrinsic elements, depicted in movie "The Pursuit of Happyness” Directed by Gabriele Muccino and the theoretical implication for English Language Teaching. Qualitative method was used to describe the dialogue/scenes that contain moral values with structural and psychological approaches. In this research, the writer used triangulation to ensure the validity of the data. The result of the research showed that and there are eighteen moral values in “The Pursuit of Happiness” movie, namely: Honesty, Self-Confidence, Responsible, Independence, Moral Courage, Humility, Critical Attitude, Peace of Ability, Love and Affection, Respect, Unselfishness and Sensitivity, Kindness and Friendliness,Strong, Belief, Loyalty, Religious, Hard Work, Dicipline and Friendly/Communicative. there are five intrinsic elements discovered in the movie, they are: Theme, Plot, Characters and Characterization, Setting, and Point of View. The theoretical implication especially for students hopefully, they can learn and practice those positive moral values in their daily life. therefore, by watching the movie, they not only get the entertainment but also moral messages which are implied in the story. Keywords: Moral values, Movie, The Pursuit of Happyness